2001
DOI: 10.1074/jbc.m103170200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ubiquitination and Degradation of p53 in Unstressed Cells through C-terminal Phosphorylation

Abstract: Previously, we found that the protein kinase C (PKC) inhibitor H7 stimulates p53 to accumulate in a form incapable of inducing transcription from p53-dependent promoters. We concluded that H7 inhibits constitutive C-terminal phosphorylation of p53, which regulates its turnover in unstressed cells. We now show that p53 and its inhibitor MDM2 (HDM2 in human cells) are together in the nuclei of H7-treated cells and can be co-immunoprecipitated. Despite this association of p53 with the ubiquitin ligase MDM2, ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 53 publications
4
35
1
1
Order By: Relevance
“…Consistent with the inability of RA to regulate IRS-1 levels in the RA-resistant MDA-MB-231 breast cancer cell line, we also failed to observe any regulation of PKC-d in these cells. Although activating PKC has not been previously reported to be required for the ubiquitination of IRS-1, the phosphorylation of p53 by PKC was shown to regulate p53 degradation by stimulating its ubiquitination (Chernov et al, 2001). Interestingly, three of the serine sites (serines 307, 323, and 574) phosphorylated by PKC-d lie within the C-terminal domain of IRS-1 that contains potential PEST sequences, as identified by a PEST-FIND program (http://emb1.bcc.univie.ac.at/ embnet/tools/bio/PESTfind/) (Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the inability of RA to regulate IRS-1 levels in the RA-resistant MDA-MB-231 breast cancer cell line, we also failed to observe any regulation of PKC-d in these cells. Although activating PKC has not been previously reported to be required for the ubiquitination of IRS-1, the phosphorylation of p53 by PKC was shown to regulate p53 degradation by stimulating its ubiquitination (Chernov et al, 2001). Interestingly, three of the serine sites (serines 307, 323, and 574) phosphorylated by PKC-d lie within the C-terminal domain of IRS-1 that contains potential PEST sequences, as identified by a PEST-FIND program (http://emb1.bcc.univie.ac.at/ embnet/tools/bio/PESTfind/) (Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of persistent suppression of PKC ␣ and isoforms, cellular protective mechanisms may be activated, resulting in p21 WAF1/CIP1 induction and subsequently causing prolonged growth arrest, perhaps by blocking the CDK/Rb/E2F axis of cell cycle progression machinery. It has been observed that the inhibition of PKC activity increases p53 stability, whereas the activation of PKC by phorbol esters blocks the DNA damage-induced accumulation of p53 (60). It is conceivable that PKC inhibition activates the counteracting phosphatase activity, which affects protein stability, through an unknown mechanism.…”
Section: Waf1/cip1mentioning
confidence: 99%
“…Examples are the destabilization of the inhibitor of NFkB (IkB), as a result of phosphorylation-dependent polyubiquitination and subsequent degradation via the proteasome pathway, 120,121 and regulation of the turnover of bcatenin and p53. 122,123 However, it remains to be established whether 4E-BP1 is ubiquitinated prior to its degradation ( Figure 2) and whether the phosphorylation status of 4E-BP1 influences its turnover in a TRAIL-sensitive manner.…”
Section: E-bp1mentioning
confidence: 99%